Pengaruh pendapatan asli daerah dan dana perimbangan serta jumlah penduduk terhadap belanja daerah dan pertumbuhan ekonomi kabupaten kutai kartanegara (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
The purpose of this study is : 1) To analyze and axamine the effect local revenue, current transfer and total population directly to regional spending. 2) To analyze and axamine the effect of local revenue, current transfer and total of population directly to economic growth. 3) To analyze and axamine indirect the effect of local revenue, current transfer and total of population on Economic growth through regional spending Kutai Kartanegara Regency. In order to test the hypothesis the authors use tools path analysis using SPSS 20. The data used in this study is the local revenue, current transfer, total of population, regional spending and economic growth Kutai Kartanegara Regency in 2005 to 2014. The results are indicating the effect local revenue, current transfer and total population is a directly influence between regional spending and economic growth. The results show that local revenues, carrent transfer and total of population is a in directly influence between economic growth through regional spending.